Manajemen Pendidikan Inklusi di SMP Negeri 7 Samarinda - Riduan, Riduan; Nurbayani, Etty; Setyoningrum, Muthia Umi (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Abstract This study is motivated by the importance of inclusive education to ensure that every child, including children with special needs, has the same rights in education. SMP Negeri 7 Samarinda has been designated as an inclusive school since 2011 and in 2023 will become one of the inclusion coordinators in Samarinda City. This study aims to examine the management of inclusive education at SMP Negeri 7 Samarinda. The type of research used is descriptive research with a qualitative approach. Data collection techniques through observation, interviews, and documentation. Data analysis techniques use the Miles, Huberman and Saldana models, namely data condensation, data presentation, and drawing conclusions. Data validity techniques use source triangulation and technique triangulation. The results of this study indicate that SMP Negeri 7 Samarinda implements inclusive education through various aspects of management. At the planning stage, schools conduct assessments of students with special needs to identify students with special needs, plan individual support, and provide opportunities for students to participate in extracurricular activities and competitions. At the organizing stage, the division of tasks between teachers and the inclusion team is carried out clearly and the grouping of tasks based on function reflects the management of education personnel. At the implementation stage, teacher motivation is increased through training in the context of education personnel management, while effective communication between schools shows the implementation of supportive communication. At the monitoring stage, there are performance standards and monitoring mechanisms in the curriculum and education personnel management, with periodic evaluations involving joint reflection, indicating sustainable environmental management and performance. The implications of this study are the need to strengthen teacher capacity through inclusive leadership, as well as continuous evaluation. Recommendations for schools include increasing training, establishing partnerships, improving inclusive facilities, and disseminating good practices to other schools. Keywords: Inclusive Education, Educational Management, Inclusive School Abstrak Studi ini dilatarbelakangi oleh pentingnya pendidikan inklusif yang menjamin bahwa setiap anak berhak memperoleh layanan yang sama dalam Pendidikan termasuk bagi anak berkebutuhan khusus. SMP Negeri 7 Samarinda ditunjuk sebagai sekolah inklusif sejak tahun 2011 dan pada tahun 2023 akan menjadi salah satu koordinator inklusi di Kota Samarinda. Penelitian ini bermaksud untuk mengkaji manajemen pendidikan inklusif di SMP Negeri 7 Samarinda. Penelitian deskriptif kualitatif ini menguunakan observasi, wawancara, dan dokumentasi dalam pengumpulan data. Teknik analisis data melalui kondensasi data, penyajian data, dan penarikan simpulan. Triangulasi sumber dan triangulasi Teknik digunakan dalam mencari data yang sah/ valid. Hasil penelitian ini menunjukkan bahwa SMP Negeri 7 Samarinda melaksanakan pendidikan inklusif melalui berbagai aspek manajemen. Pada tahap perencanaan, sekolah melakukan asesmen siswa berkebutuhan khusus untuk mengidentifikasi siswa berkebutuhan khusus, merencanakan dukungan individual, dan memberikan kesempatan kepada siswa untuk mengikuti kegiatan ekstrakurikuler dan perlombaan, Pada tahap pengorganisasian, pembagian tugas antara guru dan tim inklusi dilakukan dengan jelas dan pengelompokan tugas berdasarkan fungsi mencerminkan pengelolaan tenaga kependidikan. Pada tahap pelaksanaan, motivasi guru ditingkatkan melalui pelatihan dalam konteks manajemen tenaga kependidikan, sedangkan komunikasi efektif antar sekolah menunjukkan terlaksananya komunikasi yang mendukung. Pada tahap pemantauan, terdapat standar kinerja dan mekanisme pemantauan dalam kurikulum dan manajemen tenaga kependidikan, dengan evaluasi berkala yang melibatkan refleksi bersama, menunjukkan pengelolaan lingkungan dan kinerja yang berkelanjutan. Implikasi dari penelitian ini adalah perlunya penguatan kapasitas guru melalui kepemimpinan yang inklusif, serta evaluasi berkelanjutan. Rekomendasi bagi sekolah yaitu meningkatkan pelatihan, menjalin kemitraan, memperbaiki sarana inklusif, dan mendiseminasikan praktik baik ke sekolah lain. Kata Kunci: Pendidikan Inklusi, Manajemen Pendidikan, Sekolah Inklusi